Philosophical Approaches In Islamic Studies - Mochamad Su’eb (STAI Miftahul Ula Nganjuk, 2018)
The aim for this article is to know about A philosophical approach and about a contemporary philosophy approach in Islamic studies. This study used literature review. The results showed that there are three types of modern philosophical approaches used in Islamic studies, namely: hermeneutics, philosophical approach, and Falsafi Tafsir approach.